A prognostic model for cervical cancer based on ferroptosis-related genes - Du, Huijun; Tang, Yumei; Ren, Xiaoying; Zhang, Fan; Yang, Wei; Cheng, Le; Gao, Yunan (Frontiers in Endocrinology, 2022)
Background: Ferroptosis is widely involved in the occurrence and development of various cancers, but specific mechanism in involvement of ferroptosis in cervical cancer is still unclear. Methods: Based on the expressions of ferroptosis-related genes, a prognostic model was constructed via lasso regression, and the overall predictive performance of this model was verified. An in-depth analysis of the prognostic model is then carried out. Results: The prognostic model showed good predictive performance in both the validation set and test set. The mechanism analysis indicated that the differences in the tumor microenvironment were the basis of predictive ability of the model. Notably, CA9 mRNA was significantly over-expressed in cervical carcinoma tissues but not in normal cervix tissues. The pair of ceRNAs (CA9/ULBP2) could be involved in the carcinogenesis and development of cervical cancer, and the potential target might be hsa-miR-34a.In addition, predicted miRNAs and drugs for these DEGs. Conclusions: We constructed a prognostic model with good predictive performance based on the expression of ferroptosis-related genes. Further research found that the ceRNA pairs ULBP2/CA9 could regulate cervical cancer through hsa-miR-34a. All of these enriched the mechanism in involvement of ferroptosis in cervical cancer and might provide novel therapeutics for cervical cancer.